Cultural and Representative Policy of Sweden as an Element of Nation Branding - S. Yu. Dianina; Yu. I. Zolotukhina; G. S. Ragozin (Концепт: философия, религия, культура, 2024)
The article examines the relationship between soft power, nation branding, and educational and cultural cooperation within the framework of the Swedish Institute's policy of international cooperation to promote the country’s image abroad and strengthen the position of its reputational capital. The relevance of addressing this topic is due to the significance of the stated agenda, which, as our research has shown, influenced not only the development of cultural cooperation and academic exchanges, but also the features of building Sweden’s foreign policy image. Based on the analysis of the organization’s materials and data in reports from 2022–2023, the authors aimed to show the process of forming the priorities of the organization’s activities within the framework of the distribution of financial support and the focus of cultural and educational projects. To this end, the role and parameters of building a national brand are analyzed; changes in the topics of educational and cultural events and programs conducted by Sweden in the countries of Eastern Europe and the Baltic region are considered; the dynamics of the processes of cultural exchange between Sweden and these countries are traced; the influence of the current political situation on the volume and measures of financial assistance to them is noted; and the perception of Sweden in Russia, Eastern European and Baltic countries is characterized. The study was based on the methods of comparative analysis, discourse analysis, and case study techniques. It was concluded that in implementing a diverse range of educational and cultural programs, the Swedish Institute adheres to the principle of regionalism, which allows the implementation of such projects, taking into account the interests and needs of both Sweden and partner countries. It was shown that when determining the parameters of national branding, the Swedish Institute relies on the approach of S. Anholt, clarifying it in a number of areas. According to the findings of the study, adaptation of relevant programs for the development of cooperation with partner countries, is aimed at integrating specific Swedish values into the cultural matrix of the host cultures. The global political situation strongly influences the realization of programs, thus causing the exclusion of such an important international partner as Russia. The study confirmed the initial thesis about the relatively slow accumulation of Sweden’s reputational capital, including in the process of the Swedish Institute’s work with ‘promising’ (in the current environment) countries, as well as with the countries of Eastern Europe and the Baltic states. It is further concluded that the Swedish Institute is not only a key actor in the country's cultural and educational policy, as well as a powerful channel of soft power, but also an instrument for Sweden's positioning of itself as a moral superpower, which can be seen in many areas of its policies that go beyond fields of public diplomacy.